Microstructure measurements and estimates of entrainment in the Denmark Strait overflow plume - V. Paka; V. Zhurbas; B. Rudels; D. Quadfasel; A. Korzh; D. Delisi (Ocean Science, 2013)
To examine processes controlling the entrainment of ambient water into the Denmark Strait overflow (DSO) plume/gravity current, measurements of turbulent dissipation rate were carried out by a quasi-free-falling (tethered) microstructure profiler (MSP). The MSP was specifically designed to collect data on dissipation-scale turbulence and fine thermohaline stratification in an ocean layer located as deep as 3500 m. The task was to perform microstructure measurements in the DSO plume in the lower 300 m depth interval including the bottom mixed layer and the interfacial layer below the non-turbulent ambient water. The MSP was attached to a Rosette water sampler rack equipped with a SeaBird CTDO and an RD Instruments lowered acoustic Doppler current profiler (LADCP). At a chosen depth, the MSP was remotely released from the rack to perform measurements in a quasi-free-falling mode. Using the measured vertical profiles of dissipation, the entrainment rate as well as the bottom and interfacial stresses in the DSO plume were estimated at a location 200 km downstream of the sill at depths up to 1771 m. Dissipation-derived estimates of entrainment were found to be much smaller than bulk estimates of entrainment calculated from the downstream change of the mean properties in the plume, suggesting the lateral stirring due to mesoscale eddies rather than diapycnal mixing as the main contributor to entrainment. Dissipation-derived bottom stress estimates are argued to be roughly one third the magnitude of those derived from log velocity profiles. In the interfacial layer, the Ozmidov scale calculated from turbulence dissipation rate and buoyancy frequency was found to be linearly proportional to the overturning scale extracted from conventional CTD data (the Thorpe scale), with a proportionality constant of 0.76, and a correlation coefficient of 0.77.